PROPHYLAXIS OF DEFICIENCY OF CALCIUM IN CHILDREN - M.N. Kostyleva ("Paediatrician" Publishers LLC, 2008)
According to modern data, calcium insufficiency in children is actual problem of pediatrics. Information about calcium function, its metabolism, and the questions of influence of calcium on bone tissue and regulation of phosphorus calcium exchange is presented in this article. Special attention is given to problem of calcium insufficiency in children and its prophylaxis, including treatment with vitamin and mineral complexes. The data from study of «calcinova» in treatment of different disorders in children is presented.Key words: children, calcium, insufficiency, vitamin d, prophylaxis.